Brusatol Inhibits Proliferation and Invasion of Glioblastoma by Down-Regulating the Expression of ECM1 - Dai, Zhang’an; Cai, Lin; Chen, Yingyu; Wang, Silu; Zhang, Qian; Wang, Chengde; Tu, Ming; Zhu, Zhangzhang; Li, Qun; Lu, Xianghe (Frontiers in Pharmacology, 2021)
Brusatol (Bru), a Chinese herbal extract, has a variety of anti-tumor effects. However, little is known regarding its role and underlying mechanism in glioblastoma cells. Here, we found that Bru could inhibit the proliferation of glioblastoma cells in vivo and in vitro. Besides, it also had an inhibitory effect on human primary glioblastoma cells. RNA-seq analysis indicated that Bru possibly achieved these effects through inhibiting the expression of extracellular matrix protein 1 (ECM1). Down-regulating the expression of ECM1 via transfecting siRNA could weaken the proliferation and invasion of glioblastoma cells and promote the inhibitory effect of Bru treatment. Lentivirus-mediated overexpression of ECM1 could effectively reverse this weakening effect. Our findings indicated that Bru could inhibit the proliferation and invasion of glioblastoma cells by suppressing the expression of ECM1, and Bru might be a novel effective anticancer drug for glioblastoma cells.